2016
DOI: 10.1002/bkcs.10804
|View full text |Cite
|
Sign up to set email alerts
|

A QSAR Model for Predicting the Anti HIV‐1 Activity of TIBO Derivatives Using the Norm Indexes

Abstract: As non-nucleoside reverse transcriptase inhibitors, tetrahydroimidazo [4,5,1-jk]

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2017
2017
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…This paper was a continuation and development of our study on applying norm indexes to quantitative structure–activity relationship research for different physicochemical properties and biochemical activities about many kinds of compounds. Some models have been proposed to calculate the properties for general organic compounds and drugs, such as the aquatic toxicity for various narcotic pollutants, high affinity 5-HT 1A receptor ligands of arylpiperazine derivatives, β-cyclodextrin complex binding constants, and so forth. , In these works, the matrix norm indexes had been successfully used for predicting the toxicities and properties of diverse compounds. Here, some new norm indexes were proposed and further applied to describe the thermal conductivity of ILs at various temperatures and pressures.…”
Section: Introductionmentioning
confidence: 99%
“…This paper was a continuation and development of our study on applying norm indexes to quantitative structure–activity relationship research for different physicochemical properties and biochemical activities about many kinds of compounds. Some models have been proposed to calculate the properties for general organic compounds and drugs, such as the aquatic toxicity for various narcotic pollutants, high affinity 5-HT 1A receptor ligands of arylpiperazine derivatives, β-cyclodextrin complex binding constants, and so forth. , In these works, the matrix norm indexes had been successfully used for predicting the toxicities and properties of diverse compounds. Here, some new norm indexes were proposed and further applied to describe the thermal conductivity of ILs at various temperatures and pressures.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, a series of norm indexes descriptors had been proposed by our group, and had been used to successfully describe the quantitative structure-activity/property relationship of various organics including toxicological activity of heterocyclic compounds [10], the activity of anti-HIV reverse transcriptase inhibitors [11,12] and so on. Previous studies indicated that the proposed norm-index descriptors might be the general description of molecular structure.…”
Section: Introductionmentioning
confidence: 99%